Triangle : a novel [large type] - Steel, Danielle (Random House Large Print, 2024)
"As she approaches the milestone birthday of forty, delicate blond beauty Amanda Delanoe finds joy in running a chic contemporary art gallery in the City of Light. The only child of a French businessman and an American model, both now deceased, Amanda lives well and adores her dog, Lulu, but so far the love of her life has eluded her. Then she meets Olivier Saint Albin, a dashing publisher. At the same time, she reconnects with Tom Quinlan, an old boyfriend from her days at NYU twenty years ago, now a lawyer on sabbatical who has come to Paris to devote himself to writing a thriller. Charming Olivier is a master at the art of flirtation, but as Amanda feels herself falling for him, she learns he is married. Providing counsel and support is her friend and co-owner of the gallery, fun-loving bachelor Pascal Leblanc. When Amanda begins to receive threatening phone calls late at night, it is Pascal she turns to. Then someone breaks into her apartment on the Left Bank, and it's all too clear she is in real danger. But from whom? An old love, a new love, or a stranger? As love enters her life, so does terror. . . ."--